Legal Protection for the Aggrieved Party in a Financial Lease Agreement Due to Breach of Contract - Sari, Teresa Indah Puspita; Wijaya, Andika; Januardy, Ivans (Journal of Law, Politic and Humanities, 2025)
This paper aims to analyze the legal protection mechanisms available to parties who suffer losses as a result of a breach in financial lease agreements, and to evaluate effective dispute resolution methods, including mediation and arbitration. The research adopts a normative juridical method with a descriptive approach, utilizing data from primary and secondary legal sources. The findings indicate that breaches in financial lease agreements may occur in the form of delayed installment payments and the failure to return leased capital goods, which may result in both material and immaterial losses. A financial lease agreement must be based on a clear mutual understanding of the rights and obligations of the parties involved, so that in the event of a breach, the aggrieved party may claim damages. This principle is reflected in Article 1338 of the Indonesian Civil Code (KUH Perdata), which governs the binding force of contracts and the principle of freedom of contract, and Article 1238, which stipulates the obligation to compensate losses arising from the failure to fulfill agreed obligations. Court decisions reinforce the right of the aggrieved party to claim compensation and to demand the performance of the agreement. This paper emphasizes the importance of a clear understanding of rights and obligations in financial lease agreements in order to uphold justice and ensure the sustainability of business relationships